Generalized Difference Spaces of Non-Absolute Type of Convergent and Null Sequences - Abdulcabbar Sönmez; Feyzi Başar (Abstract and Applied Analysis)
The aim of the present paper is to introduce the spaces and of generalized difference sequences which generalize the paper due to Mursaleen and Noman (2010). These spaces are the BK-spaces of non-absolute type and norm isomorphic to the spaces and , respectively. Furthermore, we derive some inclusion relations determine the , , and duals of those spaces, and construct their Schauder bases. Finally, we characterize some matrix classes from the spaces , and to the spaces , , and c.